1992
DOI: 10.1002/ijc.2910500208
|View full text |Cite
|
Sign up to set email alerts
|

Tumor‐cell dissociation at the invasion front: A new prognostic parameter in gastric cancer patients

Abstract: Tumor-cell dissociation (TCD) is a well-known feature at the invasion front of malignant tumors, but little attention has so far been paid to its biological significance. Therefore, the aim of the present study was to score the degree of TCD at the invasion front (TCD 0-3) in a retrospective series of 445 gastric cancer patients and to compare its prognostic significance with the parameters T-stage, tumor size, grade of tumor differentiation, lymph-node involvement and vascular invasion. We could show that hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
2
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 21 publications
7
57
2
4
Order By: Relevance
“…Similar findings have been reported in patients with squamous cell carcinoma, [21][22][23] gastric cancer, 24 adenocarcinoma of the cardia, and subcardial gastric cancer. 25 The current study was a retrospective analysis, and all patients were accrued before study entry and followed, some of them for 17 years.…”
Section: Discussionsupporting
confidence: 84%
“…Similar findings have been reported in patients with squamous cell carcinoma, [21][22][23] gastric cancer, 24 adenocarcinoma of the cardia, and subcardial gastric cancer. 25 The current study was a retrospective analysis, and all patients were accrued before study entry and followed, some of them for 17 years.…”
Section: Discussionsupporting
confidence: 84%
“…LVI has been regarded as an indicator of tumour aggressiveness in several cancers. The prognostic value of LVI has been demonstrated for diverse tumour entities like gastric carcinoma, adenocarcinoma of the OGJ and squamous cell carcinoma of the oesophagus (Gabbert et al, 1992;Brucher et al, 2001;von Rahden et al, 2005). Therefore, our findings in this study may show the greater aggressiveness of C-Ca than that of D-Ca.…”
Section: Discussionsupporting
confidence: 50%
“…'1.31.32 For tumor cell differentiation (G), results are controversial.' 1,[33][34][35][36] Multivariate prognostic impact of tumor cell dissociation at invasion fronts was reported by Gabbert et al 33, and Nakane et al34 revealed significant relevance of grading. Other studies, including ours, did not find an association with prognosis.'…”
Section: Discussionmentioning
confidence: 95%